Gas-liquid and liquid-liquid separators - Stewart, Maurice (Gulf equipment guides., 2008)
This practical guide is designed to help engineers and operators develop a?feel? for selection, specification, operating parameters, and trouble-shooting separators; form an understanding of the uncertainties and assumptions inherent in operating the equipment. The goal is to help familiarize operators with the knowledge and tools required to understand design flaws and solve everyday operational problems for types of separators. The book is divided into six parts: Part one and two covers fundamentals such as: physical properties, phase behaviour and calculations. Part three through five is d.